2008
DOI: 10.1039/b811935j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 8-bromo-, 8-methyl- and 8-phenyl-dATP and their polymerase incorporation into DNA

Abstract: dATP derivatives bearing Br, Me or Ph groups in position 8 were prepared and tested as substrates for DNA polymerases to show that 8-Br-dATP and 8-Me-dATP were efficiently incorporated, while 8-Ph-dATP was a poor substrate due to its bulky Ph group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 42 publications
1
35
1
Order By: Relevance
“…Both 7‐deazaA and 8‐azaA showed sufficient yield of PCR products with the other three natural triphosphates (dT, dC, and dG; Figure S1b, c), while only 7‐deazaA led to vigorous amplification pairing with 5‐ClU compared to the other candidates, as judged from PCR using Vent ( exo ‐) DNA polymerases (Figure S1d). This observation corresponded to previously obtained data that 8‐substituted dATPs were poor substrates for DNA polymerases . At this stage, we chose one of the two DNA base pairs to be morphed into the chemically distant pairing partners, 5‐Cl‐U:7‐deazaA.…”
Section: Figuresupporting
confidence: 74%
“…Both 7‐deazaA and 8‐azaA showed sufficient yield of PCR products with the other three natural triphosphates (dT, dC, and dG; Figure S1b, c), while only 7‐deazaA led to vigorous amplification pairing with 5‐ClU compared to the other candidates, as judged from PCR using Vent ( exo ‐) DNA polymerases (Figure S1d). This observation corresponded to previously obtained data that 8‐substituted dATPs were poor substrates for DNA polymerases . At this stage, we chose one of the two DNA base pairs to be morphed into the chemically distant pairing partners, 5‐Cl‐U:7‐deazaA.…”
Section: Figuresupporting
confidence: 74%
“…As 8-substituted dATPs were previously found to be poor substrates for DNA polymerases, only derivatives bearing small bromine ( dA 8Br TP ) or methyl ( dA 8Me TP ) groups (29) were selected. On the other hand, a variety of alkyne or aryl groups are known to be tolerated by polymerases at position 7 of 7-deazaadenine dNTPs and, therefore, we have tested four examples bearing different groups varying in size and electronic effects: unsubstituted 7-deaza-dATP ( dA C7H TP ) and its 7-etnynyl ( dA C7E TP ), 7-phenyl ( dA C7Ph TP ) and 7-(3-nitrophenyl) ( dA C7NO2 TP , 19) derivatives (Chart 1).…”
Section: Resultsmentioning
confidence: 99%
“…These 5-modified derivatives of pyrimidines and 7-deazapurines were successfully incorporated to DNA by primer extension (PEX) or PCR. On the other hand, 8-substituted purine dNTPs were repeatedly shown (16,29,30) to be poor substrates and only relatively small substituents (Br or Me) were generally tolerated by the polymerase (29) and were incorporated to DNA which, despite the presence of 8-substituents, still preserved B-conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies16, 17 also demonstrated that the attachment of the redox label (ferrocene or amino/nitro groups) via a conjugated acetylene or phenylene linker enables electronic communication between the nucleobase and label, and that the redox potential responds to the incorporation to DNA. On the other hand, we14, 18 and others12c have shown that 8‐substituted purine dNTPs are poor substrates for DNA polymerases (presumably due to their preference for the syn ‐conformation and steric hindrance between the substituent and DNA backbone) and should be replaced by 7‐substituted 7‐deazapurine dNTPs. Therefore, our further efforts have been focused on the attachment of Ru(bpy) 3 complexes to the 7‐position of 7‐deaza‐2′‐deoxyadenosine and we have recently reported the synthesis and electrochemical and photophysical properties of these nucleosides 19.…”
Section: Introductionmentioning
confidence: 96%